First report of the nutritional profile and antioxidant potential of Holothuria arguinensis, a new resource for aquaculture in Europe - Roggatz, Christina C. (2017)
This work reports for the first time the nutritional profile and antioxidant potential of the edible sea cucumber Holothuria arguinensis from the North-eastern Atlantic. H. arguinensis has high levels of protein, with the amino acids profile dominated by alanine, glycine and proline and low lysine/arginine ratios. Its carbohydrate and energetic contents are also low as well as the total lipid levels, although its lipid profile is rich in polyunsaturated fatty acids (PUFA), especially arachidonic, eicosapentaenoic and docosahexaenoic acids. In addition, H. arguinensis has high levels of calcium. The water and ethanol extracts show ability to scavenge free radicals and to chelate copper and iron ions. Our results indicate that H. arguinensis has a balanced nutritional quality suitable for human consumption. In addition, it contains compounds with antioxidant potential; thus its intake can contribute for a healthy and well-balanced diet.